Penerapan Manajemen Bisnis dan Konsep Kewirausahaan dalam Pendidikan di SMP Swasta Pahlawan Nasional - Ardila, Ovi; Hakim, Maulana; Hasibuan , Ira Damayanti; Malaya , Luthfi; Aprilia , Gusti; Zauabi , Madar (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This research is motivated by seeing how important the implementation of business management is applied in the world of education. One of them is by implementing entrepreneurs . Regulation of the Minister of National Education Number 13 of 2007 concerning Principal Standards, one of which is entrepreneurial competency. This competency is the latest competency that must be possessed by the principal, in order to realize the independence of educational institutions. To be able to apply this competency is not easy. SMP Swasta Pahlawan Nasional is an independent institution because it has implemented business units. For this reason, the author conducted this research, namely to find out and answer "How is the implementation of educational business management at SMP Swasta Pahlawan Nasional". Type of research Which writer use is qualitative. In collecting data, the author uses the observation method as the main method, then supported by the interview method and documentation as supporting methods and strengthening the research results. Testing the validity of the author's data using the technique data triangulation. The conclusion of this study is that after being analyzed using theories related to the application of educational business, SMP Pahlawan Nasional is an educational institution that is able to become an independent institution. This can be proven by the application of businesses such as canteens, AK Water, tutoring, outbound, and Umrah. The income from these business units is used to repair, add, and maintain facilities and infrastructure, and the internal parties of the educational institution have been satisfied with the implementation of the business.